MODULAÇÃO DA PRODUÇÃO DE GONADOTROFINAS APÓS A EXPOSIÇÃO PRÉ-PÚBERE A ISOFLAVONAS - Oliveira, Jeane Maria de (2020)
Isoflavones are phytoestrogens present in legumes, mainly soybeans, and they have a structure similar to endogenous 17β-estradiol and therefore have the ability to interact with estrogen receptors and trigger both stimulating and inhibitory actions. Due to this fact, isoflavones (genistein, daidzein, glycitein) may have a potential endocrine disrupting effect on reproductive function by altering hormones and genes involved in the hypothalamic-pituitary-testicular axis (HPT), especially if exposure to these compounds occurs in the critical phase of prepubertal, where hormonal imprinting happens. Hormonal imbalances at this stage can lead to disturbances in adult health supporting the current concept of Origin of Health and Disease Development (DOHaD). The aim of this study was to evaluate the expression of genes and hormones related to HHT axis control after exposure to isoflavone (ISO) or genistein (GEN) isolatedly in male Wistar rats during the prepubertal period, in order to investigate the effects of these substances on the reproductive function. Forty-two rats were divided into 3 groups: control group, which received only corn oil; group exposed to 0.5, 5 or 50 mg /kg isoflavone; group exposed to 0.5 or 5 mg /kg genistein. The solutions were administered by gavage, once a day, with a volume of 0.25 ml / 100g body weight, always in the morning, from the 23rd to the 60th day of age. At the end of 60 days, the animals were euthanized under general anesthesia and then the tissues were collected and stored. Serum dosages of luteinizing hormone (LH), follicle stimulating hormone (FSH) and testosterone were measured. In the hypothalamus, the gene expression of gonadotropin releasing hormone (Gnrh1), estradiol receptor alpha (Esr1) and beta (Esr2) and androgen receptor (Ar) were evaluated. In the pituitary, the gene expression of the gonadotropin-releasing hormone receptor (Gnrhr), Lhb, Fshb, Esr1, Esr2 and Ar were evaluated. In the testis, the gene expression of the luteinizing hormone receptor (Lhcgr), stimulating follicle receptor (Fshr) and inhibin beta (Inhbb) were evaluated. Statistical analyzes were subjected to Kolmogorov-Smirnov normality tests and homoscedasticity tests by Bartle's test. The parameters were evaluated by ANOVA followed by Tukey HSD post-test. Prepubertal exposure to isoflavones and genistein led to changes with different responses in the expression of genes involved in reproductive function. There was a delay in the age in which animals entered in puberty, and increase in their weight. In the hypothalamus, the Esr1 expression was increased on ISO exposure, while Esr2 expression decreased on GEN exposure. In the pituitary, Gnrhr increased with both isoflavones, Lhb gene and Ar decreased on ISO exposure, while Fshb gene decreased with GEN. In the testicles Lhcgr expression increased in both treated groups. Serum concentrations of LH, FSH, testosterone and estradiol were also changed. Given the above results, it can be concluded that exposure to isoflavone and isolated genistein at prepubertal age compromises the normal activity of the HPT axis and may result in impaired male reproductive function.